Анализ электромагнитных процессов в однофазном трехуровневом полупроводниковом преобразователе - Брованов, С.В.; Дыбко, М.А.; Гришанов, Е.В. (Технічна електродинаміка, 2012)
The paper presents an exploration of the neutral point current without PWM harmonics in a three-level single phase NPC converter. The analysis is based on the switching states and the Space vector PWM concepts. An analytical equation for neutral point current without PWM harmonics is obtained. The equation allows to analyze the low frequency harmonics of the current.